Linking Ownership Concentration to Firm Value: Mediation Role of Environmental Performance - UTOMO, Mohamad Nur; WAHYUDI, Sugeng; MUHARAM, Harjum; HELMINA, Monica Rahardian Ary (Journal of Environmental Management and Tourism; Vol 10 No 1 (2019): JEMT Volume X Issue 1(33) Spring 2019, 2019)
Research was aimed to examine the indirect effect of ownership concentration on firm value through environmental performance. Firms with businesses at mining, manufacture, and agriculture sectors, and that listing at Indonesia Stock Exchange and participating with Environmental Performance Assessment Program (PROPER), were the sample of research. Research has given some results. Ownership concentration has positive impact non-linearly on environmental performance. Ownership concentration can increase firm value through strategy of improving environmental performance. These results supported stakeholder theory and legitimacy theory. Corporate action that adopts environmentally friendly issue was selected as strategy to create firm value.